Eventos hidrogeomorfológicos em Portugal e a sua associação com os "weather types" - Ramos, Alexandre M. (2018)
In recent years it has been possible to improve the characterization of past floods and landslides that caused human and economic impact in Portugal for the 1865-2015 period. In this regard there is an urge for a more systematic assessment of the atmospheric circulation at the synoptic scale associated to flood and landslide damaging events to correctly characterize the climatic forcing of hydro-geomorphologic risk in Portugal. Here we provide a comprehensive analysis of the atmospheric circulation based on the weather type classification, an automated version of the Lamb weather type procedure, initially developed for the United Kingdom and often named circulation weather types (CWT) and latter adapted for Portugal.